2018
DOI: 10.5713/ajas.17.0847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broussonetia papyrifera L. (paper mulberry) silage on dry matter intake, milk composition, antioxidant capacity and milk fatty acid profile in dairy cows

Abstract: ObjectiveThis study was carried out to investigate the possible application of Broussonetia papyrifera (B. papyrifera) silage as a functional feeding stuff in dairy cattle.MethodsSeventy-two Holstein cows were divided into four groups randomly and allocated to 6 pens with 3 individuals in each group and fed the original total mixed ratio (TMR) in the dairy farm or the new TMR with 5%, 10%, and 15% B. papyrifera silage, separately. Feed intake were recorded, milk and blood samples were collected, and milk compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 39 publications
13
50
2
Order By: Relevance
“…It is reported that catalytic foliage supplementation to low-quality roughages may enhance nutrient utilization in sheep [17], and foliage supplementation increased total feed intake of goats [18] with which our result of DMI was consistent. However, our results were different from the results that B. papyrifera silage decreased the DMI in dairy cattle [5], which may have been due to the replacement of low quality forage with high quality forage in diets for beef cattle, not like the low quality forage used in the diets for dairy cattle decreasing the feed intake, high quality forage could increase the DMI in beef cattle.…”
Section: Discussion Performancecontrasting
confidence: 99%
See 3 more Smart Citations
“…It is reported that catalytic foliage supplementation to low-quality roughages may enhance nutrient utilization in sheep [17], and foliage supplementation increased total feed intake of goats [18] with which our result of DMI was consistent. However, our results were different from the results that B. papyrifera silage decreased the DMI in dairy cattle [5], which may have been due to the replacement of low quality forage with high quality forage in diets for beef cattle, not like the low quality forage used in the diets for dairy cattle decreasing the feed intake, high quality forage could increase the DMI in beef cattle.…”
Section: Discussion Performancecontrasting
confidence: 99%
“…In the present study, PUFA were significantly higher in 10% and 15% groups than that in control group or 5% group (p<0.05), and it might due to the antimicrobial activities in the diet supplemented with B. papyrifera silage, as it is reported that prenylated flavonoids isolated from B. papyrifera have antimicrobial activity [36,37] which might affect the rumen microorganism by reducing the biohydrogenation of fatty acids in the rumen, and also dietary antioxidant activity might increase PUFA content in meat [38,39]. We found the similar result in milk of dairy cattle [5]. C22:6n3 (docosahexaenoic acid, DHA) of meat is higher in 5% group, 10% group and 15% group than that in control group (p<0.05).…”
Section: Amino Acids and Fatty Acids Composition In Meatsupporting
confidence: 75%
See 2 more Smart Citations
“…In this study, the MDA content of T25, T50, and T75 are lower than T0, indicating that BPS can enhance the resistance of lipid peroxidation in experimental heifers. However, another study reported that replacing WSC with 5%, 10%, and 15% BPS can improve the antioxidant indicators (T-AOC, CAT, GSH-Px, SOD) remarkably (Si et al 2018). The antioxidant capacity in the present study was not improved as the increasing of BPS content, which might due to the substitution ratio of BPS is not in a suitable range.…”
Section: Discussioncontrasting
confidence: 80%